Fluorescence cryo-microscopy: current challenges and prospects - Kaufmann, Rainer (Elsevier, 2014)
Studying biological structures with fine details does not only require a microscope with high resolution, but also a sample preparation process that preserves the structures in a near-native state. Live-cell imaging is restricted mostly to the field of light microscopy. For studies requiring much higher resolution, fast freezing techniques (vitrification) are successfully used to immobilize the sample in a near-native state for imaging with electron and X-ray cryo-microscopy. Fluorescence cryo-microscopy combines imaging of vitrified samples with the advantages of fluorescence labeling of biological structures. Technical considerations as well as the behavior of fluorophores at low temperatures have to be taken into account for developing or adapting super-resolution methods under cryo conditions to exploit the full potential of this technique.